The - Johansson, Frans (Harvard Business Review Press, 2017)
Clayton M. Christensen, bestselling author of The Innovator's Dilemma, has described The Medici Effect as "one of the most insightful books about managing innovation I have ever read. Its assertion that breakthrough principles of creativity occur at novel intersections is an enduring principle of creativity that should guide innovators in every field."